Benchmark VERCORS 2022: mechanical response of the prestressed concrete containment wall to ambient conditions - Štepán Krátký; Petr Havlásek (Acta Polytechnica CTU Proceedings)
The VERCORS benchmark was developed to provide a solid experimental basis for numerical modeling of concrete containment buildings (CCBs) to extend their lifespan. The goal of the first phase of the third benchmark is to present a blind prediction of CCB’s behavior across the whole lifespan and under periodic pressure tests. This paper summarizes the calibration of the material model based on the Microprestress-solidification (MPS) theory according to the provided laboratory experimental data. A special emphasis is given to the influence of the ambient conditions on drying creep and transient thermal creep of concrete and the calibration of the corresponding material parameters. These phenomena are studied on a representative section of the containment wall using weakly coupled thermo-hygro-mechanical analyses.